FRI0624 Musculoskeletal problems amongst train operators: a collaborative approach to identify solutions. (12th June 2018) - Erwin, J.; Howarth, J.; Chauhan, L.; Webster, A.; Woolf, A.
Abstract : Background: Transport for London (TfL) Occupational Health Dept identified musculoskeletal (MSK) problems as matters of concern in train operating staff on 3 of the underground lines (JNP). These issues were contentious and the subject of continued discussion between the management of TfL, train operators, Unions and other stakeholders. The Bone and Joint Research Group (BJRG) were invited to undertake work to provide insight into the MSK health issues of train operators from a neutral perspective. Objectives: To assess the problems and issues relating to the musculoskeletal health of train operators. Methods: A steering committee was created with representatives from the train operators, the Unions, TfL managers and other stakeholders. Participants were recruited to 6 focus groups. Separate focus groups were held for operators, managers and for other stakeholders. The groups were asked to discuss the status of their own MSK health, the impact of work on their MSK health, the support they receive from their employer and others, barriers and facilitators to maintaining MSK health, the role of managers in improving MSK health in the workplace and what interventions would improve MSK health. The focus groups were recorded transcribed and analysed using Thematic Analysis. The findings informed a survey of JNP train operators. The survey was co-produced and endorsed by the BJRG, TfL and the Unions and circulated to train operators. The survey included questions on demographics, lifestyle, work role, posture training, MSK problems, actions taken and ideas on how MSK risks could be managed and MSK health protected and improved. Results: 20% of train operators (338) completed the survey. Respondents reflected the demographic profile of the total JNP train operators. 72% reported not receiving adequate posture training. 74% experienced MSK pain, either currently or in the past. Of these 52% were currently in pain. The average number of months in pain was 59. Lower back, neck and shoulders were the most frequently reported sites of pain. 74% said the pain was caused by or worsened by work. An average of 7 days of work was lost per year due to MSK problems. 44% had not told their manager. Most respondents said their MSK health could be improved by improvements to their seating and cab ergonomics. Participants acknowledged that it is an individual's responsibility to look after their own MSK health and suggested ways to do this. These included changing position when driving, stretching, improved posture, employing good manual handling techniques, exercising outside of work and eating healthily. Conclusions: MSK problems are a significant issue among JNP train operators and structural problems are perceived to be the main cause. Operators are aware of their own role in maintaining their MSK health both at work and at home. The study illustrates that it is possible to work effectively and collaboratively with a range of workplace stakeholders to achieve a common goal of improved MSK health. The active involvement of all stakeholders throughout the process and the engagement of a neutral research organisation increased "buy-in" and gave credibility to the project. The findings are currently being considered by the steering committee to produce a series of recommendations at the policy, operational and individual level to protect the MSK health of train operators. Disclosure of Interest: None declared